Desenvolvimento dos municípios do Espírito Santo: uma visão ampliada - Dalapicola, Tiago (2019)
The thesis debates the necessity to create a new ‘development’ measurement index, more in tune with the current world, passing in this way a problematization of the multiple meanings of the term. It discusses the Human Development Index, adopted in the early 1990s, and its use for current times, then it suggests a revision with the aggregation of three new dimensions - one that denotes the sense of ‘Security’ (composed by homicide and death by traffic accidents variables); another one about the ‘Women Situation’ (in which the insertion of women in the labor market is analyzed, as well as employment, the difference in earnings relative to men and the difference in contribution to official welfare institutes) and finally one that demonstrates the ‘Demographic Structure’ (composed by total fertility rate, total dependency ratio and child mortality rate). The hypothesis from which we analyze the case of 78 municipalities in the state of Espírito Santo is that the ranking proposed by the HDI neglects other facets of the development condition, which the HDI is no longer able to fully translate. After the description of the variables composing these dimensions, the creation of an expanded development index was tested. The results obtained showed that the integration of the three proposed dimensions changes the way we view the development of municipalities in the state of Espírito Santo. A new and different ranking was produced, as the changes in the positions of the municipalities reflected the greater power of the variables and dimensions chosen to demonstrate spatial differences in terms of development. The 'Demographic Structure' dimension contributed the most to improving the positions of municipalities in the new index created, followed by the 'Security' dimension. The dimension ‘Women's Situation’ brought down the score obtained by most municipalities. The thesis was concluded with notes for possible public policies, as well as the need to balance the spatial development and the development focused on the individual.